A method for preparing negative electrode material from waste boxboard used in graphitization furnace

By performing nano-silica interlayer, reaction of magnesium powder sodium chloride and doping of N-methylpyrrolidone on the waste graphite box plate, the problem of poor performance of the waste box plate is solved, and a high-performance graphite negative electrode material with good first-term effect and circulation performance is prepared.

CN119750567APending Publication Date: 2025-04-04INNER MONGOLIA GUOXUAN ZERO CARBON TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411716143.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Due to the poor surface morphology and poor performance, waste graphite box plates cannot be used directly as high-performance graphite negative electrode material.

Method used

By mixing nano-silica and graphitization furnace with waste box plate powder, ball milling, adding magnesium powder and sodium chloride for reaction, pickling, water washing and drying, finally adding N-methylpyrrolidone and binder for granulation and shaping, carbonizing to obtain the negative electrode material.

Benefits of technology

The surface morphology and performance of the waste box plate is improved, the first effect and circulation performance of the negative electrode material are improved, and the preparation of high-performance graphite negative electrode material is realized.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a method for preparing negative electrode materials from waste boxboards for graphitization furnaces, comprising the following steps: mixing nano silicon dioxide and waste boxboard powder for graphitization furnaces, ball milling, then adding magnesium powder and sodium chloride to mix, reacting, then sequentially pickling, washing with water, and drying to obtain an intermediate material; mixing the intermediate material, N-methylpyrrolidone, and a binder, granulating, shaping, and carbonizing to obtain a negative electrode material. The present invention also discloses a negative electrode material prepared according to the above method. The negative electrode material obtained by the present invention has good first effect and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of negative electrode materials, and in particular to a method for preparing negative electrode materials from waste box plates used in a graphitization furnace. Background Art

[0002] In the process of preparing artificial graphite negative electrode materials, graphitization is a key link, which aims to convert the material into graphite. At present, the graphitization box furnace is the mainstream furnace type for graphitization. The box furnace is made of box plates made of graphite. As an important auxiliary material for heating, graphite box plates need to be used continuously, but after long-term use, their performance will gradually decline, and even faults and damage will appear on the surface. These problems eventually make the graphite box plates unable to continue to be used, thus turning them into waste graphite box plates.

[0003] At present, the recycling of waste boxboard is mainly used as a recarburizer, and its utilization value is low. Waste boxboard itself is a kind of graphite material, which has a high degree of graphitization after repeated use. Recycling it to make high-performance graphite negative electrode materials has higher economic value. However, since the waste board has been used many times, the surface morphology is poor, and the specific surface area, tap density, capacity, cycle performance and other properties are relatively poor, and it cannot be directly used as a negative electrode material. Summary of the invention

[0004] Based on the technical problems existing in the background technology, the present invention proposes a method for preparing negative electrode materials using waste box plates for a graphitization furnace. The negative electrode material obtained by the present invention has good initial efficiency and cycle performance.

[0005] The invention provides a method for preparing negative electrode materials from waste box plates for graphitization furnaces, comprising the following steps: mixing nano silicon dioxide and waste box plate powder for graphitization furnaces, ball milling, then adding magnesium powder and sodium chloride to mix, reacting, then sequentially pickling, washing with water, and drying to obtain an intermediate material; mixing the intermediate material, N-methylpyrrolidone, and a binder, granulating, shaping, and carbonizing to obtain the negative electrode material.

[0006] Preferably, the waste boxboard powder for the graphitization furnace is pretreated before use.

[0007] Preferably, the pretreatment step comprises: soaking the waste boxboard powder for graphitization furnace in a sulfuric acid aqueous solution for 1-1.5 hours, washing with water until neutral, and then keeping warm at 80-85° C. for 3-5 hours.

[0008] Preferably, the D50 particle size of the waste boxboard powder for the graphitization furnace is 10.5-12.5 μm.

[0009] The present invention pre-treats the waste boxboard powder for the graphitization furnace by soaking it in a sulfuric acid aqueous solution to change the surface roughness of the graphite through etching, and then heat-insulating it at 80-85° C. to change the microstructure of the graphite surface through thermal stress, thereby improving the surface morphology.

[0010] This treatment improves the morphology of the waste boxboard powder for the graphitization furnace, and can make it easier for the nano-silicon dioxide to form a sandwich structure with the waste boxboard powder for the graphitization furnace in the next high-energy ball milling.

[0011] Preferably, the weight ratio of nano silicon dioxide to waste boxboard powder for graphitization furnace is 2-2.5:7.5-8.

[0012] Preferably, the linear speed of the ball mill is 200-250 m / min, and the ball milling time is 1-1.5 h.

[0013] The nano-silicon dioxide and the graphitization furnace waste boxboard powder are mixed and subjected to high-energy ball milling. The graphitization furnace waste boxboard powder is made of graphite, which is extended and wrapped with the nano-silicon dioxide during the ball milling process, so that the nano-silicon dioxide is distributed between the graphitization furnace waste boxboard powder layers to form a sandwich structure.

[0014] Preferably, the weight ratio of nano silicon dioxide, magnesium powder and sodium chloride is 1:0.7-0.8:8-9.

[0015] Preferably, the reaction is carried out at 680-700° C. for 2-2.5 h in an argon atmosphere.

[0016] Magnesium powder and sodium chloride are then added to make silicon dioxide react with magnesium powder to generate nano-silicon. The high temperature generated instantaneously during the reaction causes Si to react with C to generate SiC, so that the nano-Si is sequentially coated with SiC and C layers, and forms a sandwich structure with the waste boxboard powder used in the graphitization furnace. This structure can inhibit the volume expansion of Si during the charge and discharge process, and can improve the cycle performance while improving the initial efficiency.

[0017] Preferably, the acid washing is performed 2-3 times with aqueous sulfuric acid solution, and each washing time is 1-1.5 hours.

[0018] The concentration of the above-mentioned aqueous sulfuric acid solution is 2 mol / L.

[0019] Acid washing and water washing can remove impurities and cause the interlayer spacing of graphite to expand slightly, which can promote the next step of N-methylpyrrolidone doping into the graphite.

[0020] Preferably, the binder is asphalt.

[0021] Preferably, the weight ratio of the intermediate material, N-methylpyrrolidone and the binder is 67-81:15-25:4-8.

[0022] Preferably, granulation is carried out in a nitrogen atmosphere.

[0023] Preferably, the specific procedure of granulation is: heating to 480-500° C. and keeping warm for 20-40 min, then heating to 540-560° C. and keeping warm for 20-40 min, and finally heating to 640-660° C. and keeping warm for 110-130 min.

[0024] Polyvinyl pyrrolidone molecules contain nitrogen elements. In a high-temperature inert atmosphere, carbonization reaction will occur and nitrogen atoms will be released. These nitrogen atoms can diffuse into the graphite lattice to form an N-doped graphite structure, thereby improving the electrochemical performance of the negative electrode material. In addition, polyvinyl pyrrolidone doping can make the modified artificial graphite hydrophilic, which is conducive to its application in aqueous systems.

[0025] Preferably, the D50 particle size of the shaped particles is 15.5-17.5 μm.

[0026] Preferably, the carbonization is carried out at 1100-1200° C. for 19-21 hours.

[0027] The present invention also proposes a negative electrode material prepared according to the method for preparing negative electrode material using waste box plates for a graphitization furnace.

[0028] The invention uses waste boxboard powder for graphitization furnace as raw material, which can reduce the cost; and through a suitable method, appropriate amounts of nano-Si and N are doped into the waste boxboard powder for graphitization furnace, so that the nano-Si is sequentially coated with SiC and C layers and forms a sandwich structure with the waste boxboard powder for graphitization furnace, and the N element is doped in the graphite lattice, thereby greatly improving the electrochemical performance of the negative electrode material. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is described in detail below through specific embodiments.

[0030] The following examples and comparative examples use the same batch of waste boxboard powder for graphitization furnace, and the preparation method thereof comprises: using a jaw crusher to crush the waste boxboard for graphitization furnace to less than 10 mm, and then using a coarse crusher (the motor frequency of the coarse crusher is 40-50 Hz, and the frequency of the discharge valve is 10-15 Hz) to crush the particle size to less than 3 mm, and then using an ultrafine grinder (the feeding frequency of the ultrafine grinder is 6 Hz, the current of the fan is 38-55 A, and the grading frequency is 25 Hz;) to crush and grade the particles into fine particles with a D50 of 10.5-12.5 μm, namely the waste boxboard powder for graphitization furnace.

[0031] Example 1

[0032] A method for preparing negative electrode materials from waste box plates used in a graphitization furnace comprises the following steps:

[0033] The waste boxboard powder for graphitization furnace was added into 2 mol / l sulfuric acid aqueous solution and soaked for 1 hour, washed with water until neutral, and then kept at 85℃ for 3 hours;

[0034] Nano-silicon dioxide and waste boxboard powder for graphitization furnace were mixed in a weight ratio of 2.5:7.5, transferred to a ball mill, and the ball-to-material ratio was adjusted to 15:1, and the ball milling linear speed was 250 m / min for 1 h;

[0035] Then, magnesium powder and sodium chloride (so that the weight ratio of nano-silicon dioxide, magnesium powder and sodium chloride is 1:0.8:8) are added and mixed, and reacted at 700°C for 2 hours in an argon atmosphere. After being taken out, it is washed with a 2 mol / l sulfuric acid aqueous solution for 3 times, each washing for 1 hour, and then washed with water until neutral, and dried to obtain an intermediate material;

[0036] Add the intermediate material, N-methylpyrrolidone and asphalt into the batch mixer in a weight ratio of 81:15:4, adjust the speed of the batch mixer to 16r / min and mix for 90min;

[0037] Then transfer it to the reactor and adjust the nitrogen flow rate to 0.9m 3 / h, and granulation is carried out (the specific procedure of granulation is: heating to 500℃ and keeping warm for 20min, then heating to 560℃ and keeping warm for 20min, and finally heating to 660℃ and keeping warm for 110min) to obtain particles with a D50 of 16.5-19.5μm; then shaping to obtain particles with a D50 of 15.5-17.5μm, and carbonizing at 1100℃ for 21h to obtain the negative electrode material.

[0038] Example 2

[0039] A method for preparing negative electrode materials from waste box plates used in a graphitization furnace comprises the following steps:

[0040] The waste boxboard powder for graphitization furnace was added into 2 mol / l sulfuric acid aqueous solution and soaked for 1.5 h, washed with water until neutral, and then kept at 80 °C for 5 h;

[0041] Nano-silicon dioxide and waste boxboard powder for graphitization furnace were mixed in a weight ratio of 2:8, transferred to a ball mill, and the ball-to-material ratio was adjusted to 15:1, and the ball milling linear speed was 200 m / min for 1.5 h;

[0042] Then, magnesium powder and sodium chloride (so that the weight ratio of nano-silicon dioxide, magnesium powder and sodium chloride is 1:0.7:9) are added and mixed, and reacted at 680°C for 2.5 hours in an argon atmosphere. After being taken out, it is washed twice with a 2 mol / l sulfuric acid aqueous solution, each washing for 1.5 hours, and then washed with water until neutral, and dried to obtain an intermediate material;

[0043] Add the intermediate material, N-methylpyrrolidone and asphalt into the batch mixer in a weight ratio of 67:25:8, adjust the speed of the batch mixer to 15r / min and mix for 90min;

[0044] Then transfer it to the reactor and adjust the nitrogen flow rate to 1.1m 3 / h, and granulation is carried out (the specific procedure of granulation is: heating to 480℃ and keeping warm for 40min, then heating to 540℃ and keeping warm for 40min, and finally heating to 640℃ and keeping warm for 130min) to obtain particles with a D50 of 16.5-19.5μm; then shaping to obtain particles with a D50 of 15.5-17.5μm, and carbonizing at 1200℃ for 19h to obtain the negative electrode material.

[0045] Example 3

[0046] A method for preparing negative electrode materials from waste box plates used in a graphitization furnace comprises the following steps:

[0047] The waste boxboard powder for graphitization furnace was added into 2 mol / l sulfuric acid aqueous solution and soaked for 1.3 h, washed with water until neutral, and then kept at 82 °C for 4 h;

[0048] Nano-silicon dioxide and waste boxboard powder for graphitization furnace were mixed in a weight ratio of 2.3:7.7, transferred to a ball mill, and the ball-to-material ratio was adjusted to 15:1, and the ball milling linear speed was 225 m / min for 1.3 h;

[0049] Then, magnesium powder and sodium chloride (so that the weight ratio of nano-silicon dioxide, magnesium powder and sodium chloride is 1:0.75:8.5) are added and mixed, and reacted at 690°C for 2.3 hours in an argon atmosphere. After being taken out, it is washed twice with a 2 mol / l sulfuric acid aqueous solution, each washing for 1.5 hours, and then washed with water until neutral, and dried to obtain an intermediate material;

[0050] Add the intermediate material, N-methylpyrrolidone and asphalt into the batch mixer in a weight ratio of 74:20:6, adjust the speed of the batch mixer to 15r / min and mix for 90min;

[0051] Then transfer it to the reactor and adjust the nitrogen flow rate to 1.0m 3 / h, and granulation is carried out (the specific procedure of granulation is: heating to 500℃ and keeping warm for 30min, then heating to 550℃ and keeping warm for 30min, and finally heating to 650℃ and keeping warm for 120min) to obtain particles with a D50 of 16.5-19.5μm; then shaping to obtain particles with a D50 of 15.5-17.5μm, and carbonizing at 1150℃ for 20h to obtain the negative electrode material.

[0052] Comparative Example 1

[0053] A method for preparing negative electrode materials from waste box plates used in a graphitization furnace comprises the following steps:

[0054] The waste boxboard powder for graphitization furnace was added into a 2 mol / l sulfuric acid aqueous solution and soaked for 1.3 hours, washed with water until neutral, and then kept at 82°C for 4 hours to obtain an intermediate material;

[0055] Add the intermediate material, N-methylpyrrolidone and asphalt into the batch mixer in a weight ratio of 74:20:6, adjust the speed of the batch mixer to 15r / min and mix for 90min;

[0056] Then transfer it to the reactor and adjust the nitrogen flow rate to 1.0m 3 / h, and granulation is carried out (the specific procedure of granulation is: heating to 500℃ and keeping warm for 30min, then heating to 550℃ and keeping warm for 30min, and finally heating to 650℃ and keeping warm for 120min) to obtain particles with a D50 of 16.5-19.5μm; then shaping to obtain particles with a D50 of 15.5-17.5μm, and carbonizing at 1150℃ for 20h to obtain the negative electrode material.

[0057] Comparative Example 2

[0058] A method for preparing negative electrode materials from waste box plates used in a graphitization furnace comprises the following steps:

[0059] The preparation method of the intermediate material is the same as that of Example 3;

[0060] Add the intermediate material and asphalt into the batch mixer at a weight ratio of 94:6, adjust the speed of the batch mixer to 15r / min and mix for 90min;

[0061] Then transfer it to the reactor and adjust the nitrogen flow rate to 1.0m 3 / h, and granulation is carried out (the specific procedure of granulation is: heating to 500℃ and keeping warm for 30min, then heating to 550℃ and keeping warm for 30min, and finally heating to 650℃ and keeping warm for 120min) to obtain particles with a D50 of 16.5-19.5μm; then shaping to obtain particles with a D50 of 15.5-17.5μm, and carbonizing at 1150℃ for 20h to obtain the negative electrode material.

[0062] Comparative Example 3

[0063] A method for preparing negative electrode materials from waste box plates used in a graphitization furnace comprises the following steps:

[0064] The weight ratio of nano silicon dioxide to waste boxboard powder for graphitization furnace is 3:7, and the rest is the same as in Example 3.

[0065] The negative electrode materials prepared in Examples 1-3 and Comparative Examples 1-3 were used to prepare button batteries and soft-pack batteries and test their performance. The results are shown in Table 1.

[0066] The preparation method of the button battery includes: mixing the negative electrode material: conductive carbon black (SP): carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) in a weight ratio of 95:1:1.5:2.5, coating the mixture on a copper foil, and placing the coated electrode sheet in a vacuum drying oven at 120°C for 12 hours to obtain a negative electrode sheet; assembling the obtained negative electrode sheet into a button battery in a glove box under argon protection, wherein the electrolyte is 1 mol / L LiPF6 and the solvent is EC:DEC:DMC (the volume ratio is 1:1:1); and the metal lithium sheet is the counter electrode.

[0067] Preparation method of soft-pack battery: The negative electrode material: conductive carbon black (SP): carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) are evenly mixed in a weight ratio of 95:1:1.5:2.5, applied on copper foil, and preheated and dried, rolled, dried, rolled twice, die-cut, and cut to obtain the negative electrode; the negative electrode is taken and the positive electrode and the separator are wound and assembled to obtain a soft-pack battery, wherein the positive electrode material is lithium cobalt oxide, and the charge and discharge rate is 0.2C.

[0068] Test the initial efficiency of button batteries and the cycle performance of soft-pack batteries.

[0069] Table 1 Test results

[0070] Test items Initial efficiency % 0.2C cycle 500 times capacity retention rate % Example 1 91.1 88.3 Example 2 90.8 87.8 Example 3 91.6 88.5 Comparative Example 1 84.5 77.4 Comparative Example 2 80.1 73.3 Comparative Example 3 85.3 78.8

[0071] It can be seen from Table 1 that the present invention has good first effect and cycle performance.

[0072] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing negative electrode materials from waste boxboards for graphitization furnace, characterized in that: The method comprises the following steps: mixing nano silicon dioxide and waste boxboard powder for graphitization furnace, ball milling, adding magnesium powder and sodium chloride, mixing, reacting, and then sequentially pickling, washing with water, and drying to obtain an intermediate material; mixing the intermediate material, N-methylpyrrolidone, and a binder, granulating, shaping, and carbonizing to obtain a negative electrode material.

2. The method for preparing negative electrode materials from waste boxboard for graphitization furnace according to claim 1, characterized in that: The waste boxboard powder for the graphitization furnace is used after pretreatment; preferably, the pretreatment step includes: soaking the waste boxboard powder for the graphitization furnace in a sulfuric acid aqueous solution for 1-1.5 hours, washing with water until neutral, and then keeping warm at 80-85°C for 3-5 hours.

3. The method for preparing negative electrode materials from waste boxboards for graphitization furnace according to claim 1 or 2, characterized in that: The D50 particle size of the waste boxboard powder for graphitization furnace is 10.5-12.5 μm; preferably, the weight ratio of nano silicon dioxide to the waste boxboard powder for graphitization furnace is 2-2.5:7.5-8.

4. The method for preparing negative electrode materials from waste boxboards for graphitization furnace according to any one of claims 1 to 3, characterized in that: The linear speed of the ball mill is 200-250 m / min, and the ball milling time is 1-1.5 h.

5. The method for preparing negative electrode materials from waste boxboards for graphitization furnace according to any one of claims 1 to 4, characterized in that: The weight ratio of nano-silicon dioxide, magnesium powder and sodium chloride is 1:0.7-0.8:8-9; preferably, the reaction is carried out at 680-700° C. for 2-2.5 hours in an argon atmosphere.

6. The method for preparing negative electrode materials from waste boxboards for graphitization furnace according to any one of claims 1 to 5, characterized in that: The product was pickled 2-3 times with aqueous sulfuric acid solution, each time for 1-1.5 hours.

7. The method for preparing negative electrode materials from waste boxboards for graphitization furnace according to any one of claims 1 to 6, characterized in that: The binder is asphalt; preferably, the weight ratio of the intermediate material, N-methylpyrrolidone and the binder is 67-81:15-25:4-8.

8. The method for preparing negative electrode materials from waste boxboards for graphitization furnace according to any one of claims 1 to 7, characterized in that: Granulation is carried out in a nitrogen atmosphere; preferably, the specific procedure of granulation is: heating to 480-500°C and keeping warm for 20-40 minutes, then heating to 540-560°C and keeping warm for 20-40 minutes, and finally heating to 640-660°C and keeping warm for 110-130 minutes.

9. The method for preparing negative electrode materials from waste boxboards for graphitization furnace according to any one of claims 1 to 8, characterized in that: The D50 particle size of the shaped particles is 15.5-17.5 μm; preferably, the carbonization is carried out at 1100-1200° C. for 19-21 hours.

10. A negative electrode material obtained by the method for preparing negative electrode material from waste boxboard for graphitization furnace according to any one of claims 1 to 9.

Citation Information

Cited By

  • Method for preparing lithium ion battery negative electrode material by modifying and regenerating waste graphite box plate

    CN116924386A

  • A method for modifying and recycling waste graphite box plates to prepare lithium ion battery negative materials

    CN116924386B